2014
DOI: 10.5209/rev_reaa.2013.v43.n2.44021
|View full text |Cite
|
Sign up to set email alerts
|

Alfareros de aquí o de allá: Identidad estilística y tecnológica en el valle de Pachacamac (costa central peruana)

Abstract: RESUMENEl reconocimiento de identidades étnicas y políticas previas a la conquista española en Perú se ha basado tradicionalmente en los estilos cerámicos. En la costa central, aprovechando la existencia de fuentes sobre la cuenca del Lurín, se ha sugerido que los ayllus costeños se servían preferentemente de la cerámica utilitaria de estilo Ychsma, que definiría también a la cultura del mismo nombre; los habitantes de la cabecera del valle (Huarochirí) habrían utilizado recipientes cerámicos del estilo llamad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
2
5
0
1
Order By: Relevance
“…These conclusions are in accordance with, and build upon, previous work examining the organization of production for pottery of the central coast (e.g., Makowski and Oré 2014;Makowski et al 2008Makowski et al , 2015 and for Inka Polychrome (e.g., D'Altroy and Bishop 1990). The organization was complex.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These conclusions are in accordance with, and build upon, previous work examining the organization of production for pottery of the central coast (e.g., Makowski and Oré 2014;Makowski et al 2008Makowski et al , 2015 and for Inka Polychrome (e.g., D'Altroy and Bishop 1990). The organization was complex.…”
Section: Discussionsupporting
confidence: 92%
“…41.1/8971 A03, labeled on Figure 8). Though direct comparison is not possible, is still worthwhile to compare the results of this research with those from recent work comparing ceramics from the Lurín valley and clay sources from several valleys on the central coast (Makowski and Oré 2014;Makowski et al 2008Makowski et al , 2015. That research, which evaluated only clays and not pastes using LA-ICP-MS, identified three distinct compositional groups which contained variation in decorative style as well as in macroscopic pastes, potentially indicating different potting practices or technologies were employed using the same clay.…”
Section: Comparative Datamentioning
confidence: 89%
See 1 more Smart Citation
“…Makowski 2002). These studies in general support the idea of a strategic (though indirect) Inka intrusion in the central coast, through neighbouring highland people (Makowski & Ore 2013).…”
Section: Resultssupporting
confidence: 75%
“…Scholarship by Krzysztof Makowski has contributed another level of complexity to the discussion of lomas occupations, as he argues that the Lurín Valley settlement of Pueblo Viejo was perennially settled only when it was occupied by a colony of highland mitmaqkuna , a group of forced migrants strategically resettled in the area by the Inka in the fifteenth century AD (Makowski & Oré 2013: 517; Castillo & Makowski 2019). In contraposition with the transhumant models, Makowski contends that it was only during the era of Inka imperialism that highland peoples came to occupy the site year-round, and Pueblo Viejo was abandoned following the Spanish invasion and the collapse of the Inka empire (Makowski & Oré 2013: 519). Indeed, contrary to the evidence reported at Malanche, there is no evidence of colonial occupation at Pueblo Viejo (Makowski 2002: 141).…”
Section: Long-term Trajectories: Humans and Their Landscapes On The P...mentioning
confidence: 99%